Lignocellulose adaptation drives polysaccharide biosynthesis in Tremella fuciformis: metabolomic and proteomic insights into CAZyme regulation - Xu, Yingyin; Dong, Qian; Zhang, Shilin; Xie, Liyuan; Zhang, Qian; Shu, Xueqin; Zhou, Jie; Peng, Weihong (Frontiers in Fungal Biology, 2025)
Background/ObjectivesTremella fuciformis is an edible fungus prized for its culinary value. The polysaccharide content of T. fuciformis grown on a Cyclobalanopsis substrate (TY3) was significantly higher than those grown on a mixed substrate (TF1) made of wheat bran and cottonseed hull.MethodsMetabolomics and proteomics were used to assess the effects of lignocellulose (consisting of cellulose, hemicellulose, and lignin) in different growth substrates on the polysaccharide content of T. fuciformis and its formation mechanism.ResultsTY3 had a higher lignocellulose content than TF1. The metabolites of carbohydrates and carbohydrate conjugates in TY3-grown specimens were significantly upregulated. Among the 21 identified metabolic pathways with enriched proteins, carbohydrate metabolism was the most enriched. The Carbohydrate-Active Enzyme (CAZyme) database was used to annotate 161 carbohydrate enzymes, and 67 of them were differentially expressed proteins. Carbohydrate synthetases were upregulated much more using TY3.ConclusionsTremella fuciformis grown on TY3 was verified to possess a lower ability for lignocellulose degradation (as evidenced by decreased synthesis of cellulase, xylanase, and lignin peroxidase) but a stronger ability for carbohydrate synthesis (as evidenced by increased synthesis of cellulose and hemicellulose). Our study enhances the control of polysaccharide content in T. fuciformis, thereby facilitating its processing for food applications.